2015
DOI: 10.7314/apjcp.2015.16.4.1349
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of HOXB2 and HOXB13 Proteins is Associated with HPV Infection and Cervical Cancer Progression

Abstract: Background: Cervical cancer (CeCa) is the second most common cancer in women in developing countries, and human papilloma virus (HPV) is the primary etiological factor. Aberrant expression of HOX transcription factors has been observed in several types of cancer. To date, however, no reports exist on the expression of HOXB2 and HOXB13 proteins during neoplastic progression in CeCa and its correlation with HPV infection. Materials and Methods: Expression of HOXB2 and HOXB13 proteins was assessed in tissue micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 35 publications
1
13
0
2
Order By: Relevance
“…In recent years, abnormal expression of these genes has been linked with the emergence of various, solid and hematopoietic malignancies (16)(17)(18)(19)(20). In CC, there are evidences concerning the overexpression or downregulation of HOX members, indicating its possible role during cervical carcinogenesis (Lopez et al, 2006b;Gonzalez-Herrera et al, 2015). In order to underscore differences in HOX genes expression in CC and to corroborate and complement previous findings, we performed a comparison by microarray of the mRNA expression profile of two cell lines: one derived from CC (HeLa), and the other, from non-tumorigenic keratinocytes (HaCaT).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In recent years, abnormal expression of these genes has been linked with the emergence of various, solid and hematopoietic malignancies (16)(17)(18)(19)(20). In CC, there are evidences concerning the overexpression or downregulation of HOX members, indicating its possible role during cervical carcinogenesis (Lopez et al, 2006b;Gonzalez-Herrera et al, 2015). In order to underscore differences in HOX genes expression in CC and to corroborate and complement previous findings, we performed a comparison by microarray of the mRNA expression profile of two cell lines: one derived from CC (HeLa), and the other, from non-tumorigenic keratinocytes (HaCaT).…”
Section: Discussionmentioning
confidence: 81%
“…Thus, in recent years, much effort has been devoted to the study of HOX genes and proteins and their link with cancer (Shah and Sukumar, 2010). In cervix, despite some evidences of HOX member modulation (Alami et al, 1999;Hung et al, 2003;Lopez et al, 2006b;Gonzalez-Herrera et al, 2015), the participation of these transcription factors in cervical carcinogenesis has not been explored in depth. In this work, we evaluated HOX gene deregulation in CC; in particular, we focused on HOXA9 modulation and whether this phenomenon results in an advantage for the CC cell.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that the clustered homeobox (HOX) genes are important factors in cancer pathogenesis. Numerous examples of deregulated HOX expression have been found in solid tumors, such as acute myeloid leukemia [20], head and neck squamous cell carcinoma [21], and cervical cancer [22]. Deregulation of HOX genes influences tumorigenesis and cancer cell biology through differentiation, apoptosis, receptor signaling, and other unknown mechanisms [23].…”
Section: Introductionmentioning
confidence: 99%
“…Such activation of HOX cluster members are closely linked to the process of Epithelial-Mesenchymal Transition (EMT) [22–24]. However, studies on expression profiling of HOX cluster genes in cervical cancers are mostly based on cell lines [2528], with only a couple of studies employing global gene expression profiling of cervical tissues [2930]. However, none of these studies on cervical cancer cell lines or tissues, have taken into account the presence of HPV or expression of viral oncogenes.…”
Section: Introductionmentioning
confidence: 99%